LEGAL PROTECTION FOR VICTIMS OF IDENTITY THEFT IN THE CYBER SCOPE FROM THE PERSPECTIVE OF NATIONAL CRIMINAL LAW - Deny Prabowo; Muhammad Arif Sahlepi (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study critically and in-depth examines the form and effectiveness of legal protection for victims of cyber identity theft within Indonesia's national criminal law system. Although Indonesia has legal instruments such as the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and the Personal Data Protection Law (UU PDP), in reality, victim protection remains very weak, formalistic, and non-operational. Victims of digital crime are left to struggle alone in a legal system that is slow, procedural, and lacks empathy. The offender-centered legal approach marginalizes victims' rights, even though identity theft directly impacts the honor, reputation, and security of citizens. This study uses a normative juridical method with a conceptual approach, analyzing various laws and regulations, victimology theory, legal protection doctrine, and jurisprudence. The results show that in addition to the lack of regulation in the Criminal Code regarding data as an object of crime, there is still fragmentation between institutions, weak digital forensic support, and the absence of an appropriate and victim-friendly recovery mechanism. The state cannot simply provide norms; it must also establish a concrete, swift, and responsive system to ensure that victims of digital crime receive substantive justice. This research confirms that victim protection must be a key agenda for future Indonesian criminal law reform, not merely legalistic discourse ungrounded in reality.